The Causal Influence of Life Meaning on Weight and Shape Concerns in Women at Risk for Developing an Eating Disorder - van Doornik, Sanne F. W.; Glashouwer, Klaske A.; Ostafin, Brian D.; de Jong, Peter J. (Frontiers in Psychology, 2021)
Background: Although previous studies have shown an inverse relation between life meaning and eating disorder symptoms, the correlational nature of this evidence precludes causal inferences. Therefore, this study used an experimental approach to test the causal impact of life meaning on individuals’ weight and shape concerns. Methods: Female students at risk for developing an eating disorder (N = 128) were randomly assigned to the control or the meaning condition, which involved thinking about and committing to pursue intrinsically valued life goals. A color-naming interference task was used to assess the motivational salience of body-related stimuli, and self-report measures were used to assess participants’ overvaluation of weight and shape. Results: The meaning manipulation was effective in activating intrinsically valued life goals. However, it did not result in lower self-reported overvaluation of weight and shape or lower color-naming interference effects of body-related stimuli, compared to the control condition. Post-hoc analyses suggested that baseline meaning in life was related to the impact of the manipulation. Conclusions: This experimental study did not provide evidence for a causal influence of life meaning on the overvaluation of weight and shape in a high-risk group. The current findings suggest that we first need to examine the relationship between life meaning and eating disorder symptoms in more detail, before implementing meaning interventions in clinical practice.